Religijne motywy w rewolcie Witaliana w 513-515 roku - Koczwara, Stanisław (Vox Patrum, 2004)
The short of the first twenty years of VI century of Byzantium's history when political changes in Constantinople took place was described in the article The religious motives. The leader of the rebellion indicated two aspects of his pronouncement as the most important ones. They were restoration of the religious union on the East based on resolutions of The Chalcedonian Council and recognition of the leading role of The Apostolic See in the field of guarding religious authenticity. Despite the military defeat Vitalian's revolt ended with success on the religious field.